The Active Constituent From Gynostemma Pentaphyllum Prevents Liver Fibrosis Through Regulation of the TGF-β1/NDRG2/MAPK Axis - Huang, Hui; Wang, Kuifeng; Liu, Qian; Ji, Feihong; Zhou, Hu; Fang, Shanhua; Zhu, Jiansheng (Frontiers in Genetics, 2020)
Liver fibrosis resulting from chronic liver damage constitutes a major health care burden worldwide; however, no antifibrogenic agents are currently available. Our previous study reported that the small molecule NPLC0393 extracted from the herb Gynostemma pentaphyllum exerts efficient antifibrotic effects both in vivo and in vitro. In this study, a TMT-based quantitative proteomic study using a carbon tetrachloride (CCl4)-induced mouse model of liver fibrosis was performed to identify the potential target of NPLC0393. Combining this study with bioinformatic analysis of differentially ex-pressed proteins between the CCl4 model and NPLC0393 treatment groups, we focused on the function of N-myc downstream-regulated gene 2 (NDRG2) involved in cell dif-ferentiation. In vitro studies showed that NPLC0393 prevented the TGF-β1 stimula-tion-induced decrease in the NDRG2 level in hepatic stellate cells (HSCs). Functional studies indicated that NDRG2 can inhibit the activation of HSCs by preventing the phosphorylation of ERK and JNK. Furthermore, knockdown of NDRG2 abolished the ability of NPLC0393 to inhibit HSC activation. In conclusion, these results provide in-formation on the mechanism underlying the antifibrotic effect of NPLC0393 and shed new light on the potential therapeutic function of the TGF-β1/NDRG2/MAPK signaling axis in liver fibrosis.